2015
DOI: 10.18805/ijar.5585
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and adjunct actions of nalbuphine hydrochloride in xylazine or xylazine and acepromazine premedicated horses

Abstract: The study was conducted in eighteen clinical cases of horses for diagnostic and surgical procedures requiring general anaesthesia were randomly divided into three groups, group I, group II and group III, each consisting of six cases. All the horses were premedicated with glycopyrrolate at the dose rate of 0.02 mg/kg body weight, intravenously. Horses in Group I and Group II were administered xylazine hydrochloride at the dose rate of 1.10 mg/kg body weight intravenously, whereas in Group III at the dose rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Previous studies reported the effects of combinations of xylazine and other analgesic drugs on the locomotion and movement of sheep [10] and ponies [11]. The nalbuphine-xylazine combination showed effective analgesic and sedative outcomes with cardiovascular stability in calves [7], dogs [12] and horses [13]. However, the nalbuphine- xylazine combination has not been used in camels.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the effects of combinations of xylazine and other analgesic drugs on the locomotion and movement of sheep [10] and ponies [11]. The nalbuphine-xylazine combination showed effective analgesic and sedative outcomes with cardiovascular stability in calves [7], dogs [12] and horses [13]. However, the nalbuphine- xylazine combination has not been used in camels.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike butorphanol, abuse potential with nalbuphine appears quite low, and consequently this opioid is not scheduled by the DEA (2013). Nalbuphine is a potent analgesic and also was considered a good adjunct for anesthesia in horses (Kulkarni et al 2015), cattle (Coetzee et al 2013), and dogs (Wagner et al 2008). Medetomidine is a potent a2adrenoceptor agonist with sedative and analgesic properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike butorphanol, abuse potential with nalbuphine appears quite low, and consequently this opioid is not scheduled by the DEA (2013). Nalbuphine is a potent analgesic and also was considered a good adjunct for anesthesia in horses (Kulkarni et al 2015), cattle (Coetzee et al 2013), and dogs (Wagner et al 2008). Medetomidine is a potent a2-adrenoceptor agonist with sedative and analgesic properties.…”
Section: Introductionmentioning
confidence: 99%